Penatalaksanaan Fisioterapi Pada Capsulitis Adhesiva Dextra Di RS. Angkatan Laut dr. Ramelan Surabaya - Sari, Nur Endah Purnama; , Wijianto, M. OR (2016)
Background : Frozen shoulder is a common condition that is caused due to shoulder pain and stiffness due to an inflammation of the joint capsule and can cause adhesions joint capsule. Aims of Research : To study about physiotherapy management in reducing pain, increasing range of motion and increase muscle strength in the case of Frozen Shoulder capsulitis due adhiseva using modalities Ultra Sound (US), Transcutaneus Electrical Nerve Stimulatiom (TENS) and Therapeutic Exercise (TL). Results: After terapy for about six times the obtained results of the assessment of T1 motion pain: 8, a T6: 4, tenderness T1: 5, a T6: 3, painful silence T1: 2, a T6 : 1, increase range of motion S: T1: 25-0-95, a T6: 45-0-120, F: T1: 65-0-20, a T6: 80-0-45, R (F = 90 ): T1: 20-0-25, a T6: 40-0-40, an increase in shoulder flexor muscle strength T1: 4-, a T6: 4, shoulder extensors T1: 4-, a T6: 4+, abduktor shoulder T1: 3 , a T6: 4, shoulder adductor T1: 3, a T6: 4, exorotator shoulder T1: 3, a T6: 4, endorotator shoulder T1: 3, to: 4. Conclusion: Ultrasound (US) can reduce pain in right shoulder condition caused by Frozen Shoulder capsulitis adhiseva, Transcutaneus Electrical Nerve Stimulation (TENS) can improve range of motion in his right shoulder in a state of Frozen Shoulder capsulitis due adhiseva and Exercise Therapy (TL) can increase muscle strength in the case of Frozen Shoulder capsulitis due adhiseva.